Development of mycobacterial growth inhibition assays for the early evaluation and gating of novel TB vaccine candidates - Tanner, R (2015)
Tuberculosis poses a serious global health threat, with an estimated 9 million new cases and 1.5 million deaths annually. The current vaccine, BCG, is inadequate but development of an effective alternative is severely hampered by the lack of an immune correlate of protection. Candidate vaccines are currently tested using preclinical animal models such as mice and non-human primates. Large numbers of animals are required and subjected to procedures classified as 'Moderate' in severity. Experiments are long and costly and it is unclear whether outcomes are predictive of efficacy or safety in humans. Work in this thesis describes the optimisation and evaluation of a functional in vitro Mycobacterial Growth Inhibition Assay, the MGIT, which takes into account a range of immune mechanisms and their interactions. Applying this assay, a BCG-induced reduction in mycobacterial growth was detected in humans, NHPs and mice. A correlation was observed between the in vitro MGIT response and in vivo protection from challenge in the mouse and NHP models. There was also concordance between the MGIT and epidemiological data or in vivo outcome in humans. Comparison of whole blood and PBMC compartments indicated that haemoglobin may act as a confounder and suggested a role for complement, but not antibodies, in determining mycobacterial growth. Classical monocytes and CD16- NK cells played a crucial role in PBMC MGIT. Cytokines correlating with mycobacterial growth represented a mixture of subsets, and the immunoregulatory cytokine IL-10 was highly influential. Genes correlating with mycobacterial growth were enriched for the immune response pathway, which included CD14 and HAMP, supporting the importance of monocytes and iron. Although further work is required, the MGIT assay represents a potential correlate of protection that may be applied in preclinical vaccine testing, reducing the number of animals used in challenge experiments and accelerating the development of an effective vaccine.